2016
DOI: 10.1212/wnl.0000000000002752
|View full text |Cite
|
Sign up to set email alerts
|

Gain-of-function FHF1 mutation causes early-onset epileptic encephalopathy with cerebellar atrophy

Abstract: Objective: Voltage-gated sodium channel (Na v )-encoding genes are among early-onset epileptic encephalopathies (EOEE) targets, suggesting that other genes encoding Na v -binding proteins, such as fibroblast growth factor homologous factors (FHFs), may also play roles in these disorders. Methods:To identify additional genes for EOEE, we performed whole-exome sequencing in a family quintet with 2 siblings with a lethal disease characterized by EOEE and cerebellar atrophy. The pathogenic nature and functional co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
98
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(103 citation statements)
references
References 31 publications
(52 reference statements)
4
98
0
1
Order By: Relevance
“…3 Recently, a de novo FHF1 mutation (p.R52H) was reported in early-onset EE in 2 siblings. 4 We report 3 patients from unrelated families with the same FHF1 p.R52H mutation. The 5 cases together frame the FHF1 R52H EE from infancy to adulthood.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…3 Recently, a de novo FHF1 mutation (p.R52H) was reported in early-onset EE in 2 siblings. 4 We report 3 patients from unrelated families with the same FHF1 p.R52H mutation. The 5 cases together frame the FHF1 R52H EE from infancy to adulthood.…”
mentioning
confidence: 96%
“…The table summarizes their clinical features and those of the recently published 4 original sib-pair. Salient features of the latter pair include neonatal-onset intractable epilepsy, profound intellectual disability, severe feeding difficulties, MRI initially unremarkable and subsequently exhibiting cerebellar atrophy, ataxia, and death in SE.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 The mutation is a de novo heterozygous G>A transition at position 155 of the complementary DNA (NM_004113) which results in a p.R52H missense substitution. Sanger sequencing was performed in both trios and confirmed that the mutation was only present in the affected probands.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, WES in a family quintet with 2 affected siblings with early-onset epileptic encephalopathy (EOEE) and cerebellar atrophy identified fibroblast growth factor 12 ( FGF12 , also known as FHF1 ) as a putative gene responsible. 2 A de novo gain-of-function variant (p.R52H) was found in 2 affected siblings with lethal disease. FGF12 encodes a cytosolic protein that interacts with neuronal sodium channels and increases their voltage-dependent fast inactivation.…”
mentioning
confidence: 99%